Biological monitoring from the perspective of nursing managers - Caroline Vieira Claudio; Leila Maria Mansano Sarquis; Louise Aracema Scussiato; Fernanda Moura D’Almeida Miranda (Rev Rene)
This is a qualitative, descriptive and exploratory research aimed at analyzing nursing managers’ knowledge on adherence to nursing workers monitoring after occupational accidents due to exposure to biological fluids, seeking to recommend strategies to reduce monitoring abandonment. We interviewed twelve nursing managers from health institutions in the city of Curitiba-Paraná, from August to November 2010, and after the transcription of these interviews we carried out a thematic analysis. Results showed that eight out of the twelve interviewed nurses have no worker supervision control with regards to complete post-exposure monitoring. The interaction between the victim’s workplace and health institutions was proposed to improve monitoring. Therefore, nurse managers and technical managers should raise awareness and monitor workers seeking to achieve adherence to full accompaniment policies and compliance with the current legislation in order to make this practice more efficient.